Level of Utilization of Main and Functional Facilities Coastal Fishing Port Tobelo North Halmahera District - Tou, Mujais; Karman, Amirul; Kaidati, Bahar (Agrikan Jurnal Agribisnis Perikanan, 2021)
The research was conducted at the Tobelo coastal fishing port, North Halmahera Regency, for one month, namely in November 2020. The research method used was a case study. The condition of the existence of basic facilities at PPP Tobelo, namely the length of the pier having a capacity of 80.00 m, an area of the port pool of 100 m2, the depth of the pier waters -5.00. The existing condition of functional facilities is an ice factory consisting of 2 units (each with a capacity of 5 tonnes a day), ABF consisting of 2 units (each with a capacity of 5 tonnes / 24 hours) and cold storage consisting of 2 units (each with a capacity of 50 tonnes). The utilization rate of the length of the pier and port pond exceeds the optimal limit of the installed capacity, then the utilization rate of the depth of the pier waters, ice factory, air blast freezer, and cold storage is not optimal.